Improving the Hip Fracture Risk Prediction Through 2D Finite Element Models From DXA Images: Validation Against 3D Models - Terzini, Mara; Aldieri, Alessandra; Rinaudo, Luca; Osella, Giangiacomo; Audenino, Alberto L.; Bignardi, Cristina (Frontiers in Bioengineering and Biotechnology, 2019)
Osteoporotic fracture incidence represents a major social and economic concern in the modern society, where the progressive greying of the population involves an highly increased fracture occurrence. Although the gold standard to diagnose osteoporosis is represented by the T-score measurement, estimated from the Bone Mineral Density (BMD) using Dual-energy X-ray Absorptiometry (DXA), the identification of the subjects at high risk of fracture still remains an issue. From this perspective, the purpose of this work is to investigate the role that DXA-based two-dimensional patient-specific finite element (FE) models of the proximal femur, in combination with T-score, could play in enhancing the risk of fracture estimation. With this aim, 2D FE models were built from DXA images of the twenty-eight post-menopausal female subjects involved. A sideways fall condition was reproduced and a Risk of Fracture ((RF) ̂) was computed on the basis of principal strains criteria. The identified (RF) ̂ was then compared to that derived from the CT-based models developed in a previous study. The 2D and 3D (RF) ̂ turned out to be significantly correlated (Spearman’s ρ=0.66,p<0.001), highlighting the same patients as those at higher risk. Moreover, the 2D (RF) ̂ resulted significantly correlated with the T-score (Spearman’s ρ=-0.69,p<0.001), and managed to better differentiate osteopenic patients, drawing the attention to some of them. The Hip Structural Analysis (HSA) variables explaining the majority of the variance of the 2D and 3D fracture risk were the same as well, i.e. neck-shaft angle and narrow neck buckling ratio. In conclusion, DXA-based FE models, developable from currently available clinical data, appear promising in supporting and integrating the present diagnostic procedure.